(untitled) (REMUNOM, 2026)
This study investigates artificial intelligence (AI) as a strategic tool for the development of teachers’ digital competencies (TDC) in mathematics education. The central question is how AI can assist in developing these competencies from the perspective of the European DigCompEdu framework. The objective was to propose a matrix of potentialities that integrates the theoretical framework of DigCompEdu with the functionalities of AI tools (such as ChatGPT, Gemini, and GeoGebra). Methodologically, the research is a qualitative, propositional study based on a literature review and a prompt engineering protocol consisting of 36 rounds of systematic functional testing. The results culminated in the creation of a matrix of potentialities that serves as a pedagogical auditing tool, demonstrating how AI can operate in six areas of competency: professional engagement, digital resources, teaching and learning, assessment, learner empowerment, and fostering students’ digital competencies. It was concluded that AI functions as a "cognitive scaffold," enabling sophisticated didactic transposition and transforming teachers’ roles into those of mediators and critical auditors of pedagogical data—essential for autonomy and inclusion in the post-pandemic educational scenario.